Acadia National Park - Fazio, Wende (New York Children's Press, 1998)
Describes the history, landscape, wildlife, and activities available for visitors to Acadia National Park
American Corner
Organizations and online sites: p. 45
Includes bibliographical references (p. 44) and index
5 8 11 18
Keywords: National parks and reserves; Acadia National Park (Me.); Acadia National Park (Me.) -- Juvenile literature